0
$\begingroup$

Let f $\in$ $C^1[-1,1]$. Evaluate

$$\lim_{n\rightarrow \infty}\frac{1}{n}\sum_{k=1}^{n}f'(\frac{k}{3n})$$


My approach

I have tried to convert the summation into a Riemann Integral as follows:

\begin{align*} \implies 3\cdot \lim_{n\rightarrow \infty} \sum_{k=1}^{n}f'\left(\frac{k}{3n}\right)\cdot \left( \frac{k}{3n}-\frac{k-1}{3n}\right) \end{align*}

By partitioning the interval $[0,1/3]$ into $(n-1)$ intervals. But how do I show that this is the Riemann Sum that corresponds to the integral:

$$\int_0^{1/3}f'(x)dx$$

$\endgroup$
  • $\begingroup$ Let $g(x) = f'(x/3)$, then the limit is $\int_0^1 g(x)dx = \int_0^1 f'(x/3)dx$, now do a change of variable. $\endgroup$ – user384138 Jan 20 '17 at 14:50
  • $\begingroup$ @OpenBall How do I show that the limit is $\int_0^1 g(x) dx$ after I substituted $g(x)=f'(x/3)$ in the last step I showed. $\endgroup$ – mm-crj Jan 20 '17 at 15:06
1
$\begingroup$

You already have a Riemann sum (or almost). Let $g\colon[-3,3]\to\mathbb{R}$ be the $\mathcal{C}^1$ function defined by $g(x) = f(\frac{x}{3})$. Then $g'(x) = \frac{1}{3}f'(\frac{x}{3})$ for all $x\in[-1,1]$, and for $n\geq 1$ $$\begin{align} \frac{1}{n}\sum_{k=1}^n f'\left(\frac{k}{3n}\right) &= 3\cdot \frac{1}{n}\sum_{k=1}^n \frac{1}{3}f'\left(\frac{k}{3n}\right) = 3\cdot \frac{1}{n}\sum_{k=1}^n g'\left(\frac{k}{n}\right)\\&\xrightarrow[n\to\infty]{} 3\int_0^1 g'(x)dx = 3\left(g(1)-g(0)\right) = 3\left(f\left(\frac{1}{3}\right)-f(0)\right) \end{align}$$


As sanity checks, let us try for

  • $f$ being the identity function: then, $$\begin{align} \frac{1}{n}\sum_{k=1}^n f'\left(\frac{k}{3n}\right) &= \frac{1}{n}\sum_{k=1}^n 1 = 1 \\&\xrightarrow[n\to\infty]{} 1= \boxed{3\left(f\left(\frac{1}{3}\right)-f(0)\right)} \end{align}$$ indeed.

  • $f$ being the the square function, $f(x)=x^2$. Then $$\begin{align} \frac{1}{n}\sum_{k=1}^n f'\left(\frac{k}{3n}\right) &= \frac{2}{3}\cdot \frac{1}{n}\sum_{k=1}^n \frac{k}{n} \\&\xrightarrow[n\to\infty]{} \frac{2}{3}\cdot\frac{1}{2} = \frac{1}{3} = 3\left(f\left(\frac{1}{3}\right)-f(0)\right) \end{align}$$ again.

$\endgroup$
  • $\begingroup$ Thanks for the detailed explanation. :) $\endgroup$ – mm-crj Jan 20 '17 at 15:41
  • $\begingroup$ Glad it helped! $\endgroup$ – Clement C. Jan 20 '17 at 15:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.